Chess and basic education: an extension proposal for solving and creating mathematical problems in public schools - Paula, Diego Pauli de; Furlani, João Carlos (Guará Journal, 2026)
This study aimed to develop a university outreach program centered on educational chess and mathematical problem solving, designed as a partnership between universities and public schools. This methodological, theoretical-propositional study was based on a postgraduate project in educational chess, Brazilian outreach policy documents, and scientific literature on mathematics education, games, and chess instruction. The resulting program, “Chess in dialogue: playing, thinking, and posing problems,” comprises 48 semester hours, 16 community workshops, and five blocks: listening and agreement building; chess initiation; strategies and heuristics; mathematical investigations on the board and problem posing; and a community showcase with feedback. Team preparation, low-cost materials, accessibility adaptations, and participatory monitoring indicators were also defined. Chess may provide a coherent outreach environment for communication, decision making, and problem solving, provided that its benefits are not assumed in advance, heuristics are explicitly mediated, and the community participates in defining, evaluating, and continuing the initiative.
Keywords: University outreach; Mathematics education; Chess; Problem solving; Educational games